PEMBERIAN PENYULUHAN DAN KONSELING TENTANG SAYUR DAN BUAH UNTUK PENCEGAHAN HIPERTENSI LANJUT USIA DI WILAYAH KERJA PUSKESMAS ASTAMBUL MARTAPURA - Yasir Farhat; Marwan Syah; Rusmini Yanti (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2022)
Hypertension is a condition in which a person experiences an increase in blood pressure above normal which results in an increase in morbidity (morbidity) and death (mortality). Hypertension in the elderly is mostly isolated systolic hypertension (HST), increasing systolic pressure causes a high probability of stroke even though the diastolic pressure is within normal limits. The purpose of the activity is to provide Counseling and Counseling on Vegetables and Fruits for the Prevention of Hypertension in the Elderly in the Working Area of ??the Astambul Martapura Community Health Center. The activity method uses group education methods in the form of counseling and individual (individual) approaches with counseling so that contact between the elderly and officers is more intensive The results of the activity did not show a significant change in the pattern of eating vegetables and fruit after 1, 2, and 3 months of counseling and counseling, while there was a significant change in blood pressure after 1, 2, and 3 months of counseling and counseling.